Disparity in dental attendance among older adult populations: a comparative analysis across selected European countries and the USA - Manski, Richard; Moeller, John; Chen, Haiyan; Widström, Eeva; Listl, Stefan (International dental journal, 2016)
Background The current study addresses the extent to which diversity in dental attendance across population subgroups exists within and between the USA and selected European countries. Method The analyses relied on 2006/2007 data from the Survey of Health, Ageing and Retirement in Europe (SHARE) and 2004-2006 data from the Health and Retirement Study (HRS) in the USA for respondents ≥ 51 years of age. Logistic regression models were estimated to identify impacts of dental-care coverage, and of oral and general health status, on dental-care use. Results We were unable to discern significant differences in dental attendance across population subgroups in countries with and without social health insurance, between the USA and European countries, and between European countries classified according to social welfare regime. Patterns of diverse dental use were found, but they did not appear predominately in countries classified according to welfare state regime or according to the presence or absence of social health insurance. Conclusions The findings of this study suggest that income and education have a stronger, and more persistent, correlation with dental use than the correlation between dental insurance and dental use across European countries. We conclude that: (i) higher overall rates of coverage in most European countries, compared with relatively lower rates in the USA, contribute to this finding; and that (ii) policies targeted to improving the income of older persons and their awareness of the importance of oral health care in both Europe and the USA can contribute to improving the use of dental services.
First published 14 October 2015
Gesehen am 07.05.2020